Transition from n- to p-type conduction concomitant with enhancement of figure-of-merit in Pb doped bismuth telluride: Material to device development - Anil K. Bohra; Ranu Bhatt; Ajay Singh; Shovit Bhattacharya; Ranita Basu; K.N. Meshram; Shaibal K. Sarkar; Pramod Bhatt; P.K. Patro; D.K. Aswal; K.P. Muthe; S.C. Gadkari (Materials & Design, 2018)
The majority of industrial, automobile processes, electrical appliances emit waste heat in the low-temperature range (<573 K), hence efficient thermoelectric materials operating in this range are highly needed. Bismuth telluride (Bi2Te3) based alloys are conventional thermoelectric material for the low-temperature application. The pure Bi2Te3 sample synthesized in this work exhibits n-type conduction. We demonstrate that by small doping of Pb at Bi site a transition in electrical transport form n- to p-type is observed. The figure-of-merit (ZT) of n-type Bi2Te3 is ~0.47 and optimized Bi1.95Pb0.05Te3 exhibit p-type conduction with enhanced ZT of ~0.63 at 386 K. The conversion efficiency of Bi1.95Pb0.05Te3 based single thermoelement with hot pressed Ni/Ag electrical contacts was found to be ~4.9% for a temperature difference (ΔT) of 200 K. The efficiency was further enhanced to ~12% (at ΔT ~ 494 K) in the segmented thermoelement consisting of Bi1.95Pb0.05Te3 and (AgSbTe2)0.15(GeTe) 0.85 (i.e. TAGS-85). Keywords: Thermoelectric power generation, Seebeck effect, Figure-of-merit, Doping, Vacancies, Electrical contacts